BioEssays 11/2020. (21st October 2020) - Patteson, Alison E.; Vahabikashi, Amir; Goldman, Robert D.; Janmey, Paul A.
Abstract : In article 2000078, Alison Patteson et al. review the various functions of filamentous and non‐filamentous vimentin. While the mechanical and intracellular roles of vimentin – such as providing protection of the nucleus and elasticity to the cytoskeleton – are well documented, recent studies point towards additional, non‐mechanical functions for vimentin. These functions include signaling roles in wound healing, lipogenesis and sterol processing as well as a role in pathogen infection.